Accuracy of bleeding scores for patients presenting with myocardial infarction: a meta-analysis of 9 studies and 13 759 patients - Taha, Salma; D’Ascenzo, Fabrizio; Moretti, Claudio; Omedè, Pierluigi; Montefusco, Antonio; Bach, Richard G.; Alexander, Karen P.; Mehran, Roxana; Ariza-Solé, Albert; Zoccai, Giuseppe Biondi; Gaita, Fiorenzo (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Due to its negative impact on prognosis, a clear assessment of bleeding risk for patients presenting with acute coronary syndrome (ACS) remains crucial. Different risk scores have been proposed and compared, although with inconsistent results. Aim: We performed a meta-analysis to evaluate the accuracy of different bleeding risk scores for ACS patients. Material and methods : All studies externally validating risk scores for bleeding for patients presenting with ACS were included in the present review. Accuracy of risk scores for external validation cohorts to predict major bleeding in patients with ACS was the primary end point. Sensitivity analysis was performed according to clinical presentation (ST segment elevation myocardial infarction (STEMI) and non-ST segment elevation myocardial infarction (NSTEMI)). Results : Nine studies and 13 759 patients were included. CRUSADE, ACUITY, ACTION and GRACE were the scores externally validated. The rate of in-hospital major bleeding was 7.80% (5.5–9.2), 2.05% (1.5–3.0) being related to access and 2.70% (1.7–4.0) needing transfusions. When evaluating all ACS patients, ACTION, CRUSADE and ACUITY performed similarly (AUC 0.75: 0.72–0.79; 0.71: 0.64–0.80 and 0.71: 0.63–0.77 respectively) when compared to GRACE (0.66; 0.64–0.67, all confidence intervals 95%). When appraising only STEMI patients, all the scores performed similarly, while CRUSADE was the only one externally validated for NSTEMI. For ACTION and ACUITY, accuracy increased for radial access patients, while no differences were found for CRUSADE. Conclusions : ACTION, CRUSADE and ACUITY perform similarly to predict risk of bleeding in ACS patients. The CRUSADE score is the only one externally validated for NSTEMI, while accuracy of the scores increased with radial access.